Chile - Financial Sector Assessment Program, November 2021 : Pension System - Cohen, Charles; Dijkman, Miquel (World Bank, Washington, DC, 2022)
The pension system in Chile is known for the 1980 establishment of a defined contribution, individual account system managed by private pension funds (AFPs). In 2008 a major reform of the system took place to address issues of low coverage and low pension rates. In 2019 the Solidarity Pension rate was raised to the poverty rate following severe social unrest which included protests against the pension system, whilst in 2020-2021 large emergency withdrawals have been allowed from the funds in the context of the Coronavirus (COVID-19) pandemic. The funded pension system has made a significant contribution to financial sector diversification and stability, while promoting sustained economic growth and development, and should be maintained. Further withdrawals should be avoided, and the contribution rate increased. An employer contribution of at least the proposed 6 percent is needed to improve pension levels and could be managed by a public entity with strong governance in a way which complements the AFP system. A non-profit AFP could be established to compete with and act as a standard setter for the private funds managing the existing 10 percent employee contributions. To contribute to long-term investment and financial stability, the multifondos investment regulation should be replaced with a ‘target date’ default, delineated by retirement age, along with a limited number of investment options, with switching contained and some access to funds for specific purposes strictly controlled. The risk-based supervision model of the SP should be recalibrated to further transition from a compliance approach.